Comparison of results after surgical repair of acute and chronic ulnar collateral ligament injury of the thumb - EROL, BÜLENT (ELSEVIER, 2014)
This study sought to demonstrate that successful outcomes can be achieved with the new technique presented here for chronic ulnar collateral ligament (UCL) injury of the thumb metacarpophalangeal (MCP) joint, as well as with K-wire pinning for acute UCL injury. We followed 19 patients who suffered an UCL rupture (mean follow-up: 14.26 +/- 4.65 months) and 32 patients who presented with UCL avulsion fracture (mean follow-up: 16.81 +/- 7.54 months). We used a free tendon graft for UCL reconstruction in the UCL rupture group. Both ends of the graft were stabilized with bioabsorbable suture anchors, which were used as biotenodesis interference screws. Closed reduction and K-wire fixation was used in UCL avulsion fracture group. There were no statistically significant differences between operated and contralateral healthy thumb MCP joint in both groups in the grip strength, tip pinch strength, flexion, extension, ulnar deviation, and radial deviation movements at final follow-up. Grip strength, tip pinch strength, ulnar deviation and radial deviation were significantly better in the avulsion group than the rupture group. All patients regained full stability at the MCP joint in avulsion group; 16 patients regained full stability and 3 patients presented with mild laxity (less than 10 degrees laxity) in rupture group. Glickel grading scale used as a functional score was excellent for 30 patients and good for 2 patients in avulsion group; it was excellent for 17 patients and good for 2 patients in rupture group. Our study shows that closed reduction and percutaneous K-wire fixation of acute displaced large UCL avulsion fracture is a simple technique and achieves adequate stability of UCL. For UCL rupture, free tendon reconstruction with bioabsorbable suture anchors provides adequate stability and stable fixation within the tunnels. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: Ulnar collateral ligament; Thumb; Free tendon graft; Rupture; Avulsion fracture; Surgery; METACARPOPHALANGEAL JOINT; AVULSION FRACTURES; DISPLACEMENT; INSTABILITY; RUPTURE